1998
DOI: 10.1111/j.1530-0277.1998.tb03696.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Relapse to Substance Abuse as a Function of Personality Dimensions

Abstract: The goal of the present study was to determine whether personality traits are related to return to heavy drinking or drug use following treatment for substance abuse. Personality characteristics of one hundred and eight patients residing on an inpatient substance abuse treatment program were assessed. Personality traits were examined using the 5-factor model of personality as measured by the NEO-Personality Inventory. These patients were then followed for 1 year after discharge from the treatment program. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
45
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 38 publications
8
45
1
1
Order By: Relevance
“…For instance, with regard to alcohol use in college, Park, Sher, Wood, and Krull (2009) found that "individuals high in impulsivity/novelty seeking appear to select into the Greek system because of its drinking-centered atmosphere" and that these individuals "increase their drinking through selection into a high-risk environment, which then exerts further influence on drinking" (p. 251). Finally, personality factors may be helpful in identifying individuals who are most at risk for relapse following treatment (e.g., Cannon, Keefe, and Clark, 1997;Fisher, Elias, and Ritz, 1998;Muller, Weijers, Boning, and Wiesbeck, 2008). For instance, Bottlender and Soyka (2005) found that alcohol-dependent patients with higher scores on the trait of neuroticism and lower scores on conscientiousness were significantly more likely to relapse following treatment.…”
Section: Empirical Relevance To Addictionmentioning
confidence: 99%
“…For instance, with regard to alcohol use in college, Park, Sher, Wood, and Krull (2009) found that "individuals high in impulsivity/novelty seeking appear to select into the Greek system because of its drinking-centered atmosphere" and that these individuals "increase their drinking through selection into a high-risk environment, which then exerts further influence on drinking" (p. 251). Finally, personality factors may be helpful in identifying individuals who are most at risk for relapse following treatment (e.g., Cannon, Keefe, and Clark, 1997;Fisher, Elias, and Ritz, 1998;Muller, Weijers, Boning, and Wiesbeck, 2008). For instance, Bottlender and Soyka (2005) found that alcohol-dependent patients with higher scores on the trait of neuroticism and lower scores on conscientiousness were significantly more likely to relapse following treatment.…”
Section: Empirical Relevance To Addictionmentioning
confidence: 99%
“…2. Extraversion, neuroticism and conscientiousness by means of the NEO Questionnaire (see Fisher et al 1998) -session 1. 3.…”
Section: Methodsmentioning
confidence: 99%
“…The Five-Factor model consists of five main personality traits: Openness, Conscientiousness, Extraversion, Agreeableness, and Neuroticism (see Table 1 for a list of characteristics associated with each of these factors). Cross-sectional assessments of personality have found that individuals in treatment for alcohol dependence are characterized by high Neuroticism and low Conscientiousness (Fisher, Elias, & Ritz, 1998;Martin & Sher, 1994), with some investigators also finding evidence of low Agreeableness (McCormick, Dowd, Quirk, & Zegarra, 1998).…”
mentioning
confidence: 98%
“…Knowing the relative risk for relapse of personality informs knowledge about the course of recovery and treatment decision making. Fisher et al (1998) were the first to investigate the influence of Five-Factor model traits on relapse in individual with alcohol dependence. The study followed 108 participants for one year after completion of an inpatient treatment program, using clinical judgment of whether participants were actively using alcohol or drugs as the relapse outcome measure.…”
mentioning
confidence: 99%
See 1 more Smart Citation